Paradigma Pendidikan Politik Antikorupsi dan Kesetaraan Gender di Partai Politik - Satria Buana, Mirza; Erlina, Erlina; Yulia Rahman, Eka (Integritas : Jurnal Antikorupsi, 2021)
Political education for women politicians is ineffective because women are still considered merely as an ‘object’ to perpetuate patriarchy political dynasty. This study utilizes a legal inter-diciplinary methodology. It selects five political parties. Respondents are female politicians who have experiences on political education, anti-corruption and gender equality issues. Most of political parties are dependent with political figure as a ‘strong leader’. Political education’s curriculum is a doctrinization of parties’ political figures. It lacks of anti-corruption and gender equality perspectives. Reform should start from within by changing its paradigm into member-based mass political party, so political education can leverage female politicians.